NMB target level tracking via an optimization based control law - J. Almeida (2015)
In this paper a state-feedback law for the control of the neuromuscular blockade level is presented. The control law is designed based on an optimal problem that is relaxed into a semi-definite program using a change of variable. For that purpose a parsimoniously parameterized model is used to describe the patient?s response to a muscle relaxant. Due to clinical restrictions the controller action begins when the patient recovers after an initial drug bolus. The results obtained encourage the implementation of this controller in the clinical environment even in the presence of noise.